Tantangan dan Solusi dalam Pengajaran Pendidikan Moral di Sekolah Dasar - Suwandi (Yayasan Darussalam Bengkulu, 2024)
This study aims to identify the main challenges in teaching moral education in elementary schools and develop effective solutions to overcome these challenges. Moral education at the elementary level is becoming increasingly important amidst rapid social change and technological developments, which often disrupt the moral values taught. This study uses a qualitative approach with a case study method involving teachers, students, and parents as respondents. Data collection was carried out through in-depth interviews, classroom observations, and document studies, which were then analyzed using thematic analysis techniques. The results of the study indicate that the main challenges in moral education in elementary schools include limited time in the curriculum, low student interest, the negative influence of social media, and lack of support from families. To overcome these challenges, the proposed solutions include the integration of moral education in all subjects, increased collaboration between teachers and parents, and the implementation of a more contextual and experience-based learning approach. By implementing these solutions, moral education is expected to be more effective in shaping students' character and positive values from an early age.